NAVIGATING MODERN LINGUISTIC CHALLENGES: INNOVATIONS IN FOREIGN LANGUAGE TEACHING - Bekkulova Hojar Zayniddinovna (Western European Studies, 2024)
This paper explores how language teaching adapts to globalization and technology. It delves into the impact of technology on language learning, including apps and virtual classrooms. Additionally, it highlights the significance of cultural sensitivity and introduces pedagogical strategies like cultural immersion and authentic materials. By embracing these innovations, educators can address modern linguistic challenges and prepare students for a multicultural world
Keywords: technology-mediated; cultural nuances